Income inequality in China and its influencing factors - Wang Xiaolu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
While the average level of income per capita has increased in China rapidly, income inequality is becoming a more serious problem that may threaten social stability and the sustainability of economic development. This paper examines the existence in China of an inverted U-shaped curve for income inequality and economic development (known as the Kuznets curve), and tests for the effects of a series of hypothesized factors influencing income inequality. Panel data modelling based on provincial level data predicts an increasing trend of inequality in the future, but cannot confirm an alleviation of inequality in the long run. It is found that a series of factors relating to growth, institutional arrangements, income redistribution and social security systems, and provision of public goods and infrastructure, is either responsible for the increase, or contributes to the reduction, in inequality. – inequality ; China ; Kuznets curve
Keywords: O18; O53; P24; 330; Einkommensverteilung; Kuznets Kurve; China